Developing a Measure of Industrial Relations Climate - Dastmalchian, Ali; Adamson, Raymond; Blyton, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This study aims at devising a set of scales for measuring the climate of industrial and labour relations within organizations